Anxiety and Depression and their Predictors among School Adolescents of Kathmandu, Nepal - Bajracharya, Shanti; Shakya, Sujata; Nagarkoti, Liza; Kumari Ban, Rita; Regmi, Kalpana (Journal of Nepal Paediatric Society, 2022)
Introduction: Adolescence is a vulnerable period in which different physical, psychological and behavioral changes occur contributing to mental health issues. Depression and anxiety occur more commonly than would be expected by chance in children and adolescents. Undetected and untreated mental disorders can impair one’s ability to perform at school or work place, cope with daily life activities and can lead to severe mental disorders and related consequences. The aim of this study was to assess the levels of anxiety and depression and their predictors among the adolescents of Kathmandu, Nepal. Methods: A cross-sectional study was conducted in different higher secondary schools of Kathmandu. Cluster random sampling method was used to select 482 students of Grade XI and XII. Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI)-II were used to assess the levels of anxiety and depression. Results: Among 482 students, 230 (47.7%) were females and 252 (52.3%) were males with mean age of 17.25 (± 1.01) years. Majority (38.6%) had minimal anxiety and 11.6% had severe anxiety. On the other side, 45.9% had no depression and 16.4% had severe depression. Grade, sex, health problem, use of gadget and academic performance are found to be the predictors of anxiety, while, the predictors of depression are age, sex, health problem and academic performance. Conclusions: Anxiety and depression are found prevalent among the adolescents, which need to be explored and addressed immediately through appropriate measures. Psychological counseling and support services should be available to vulnerable students.